Correcting India's Chronic Shortage of Drug Inspectors to Ensure the Production and Distribution of Safe, High-Quality Medicines - Abhay B. Kadam; Karen Maigetter; Roger Jeffery; Nerges F. Mistry; Mitchell G. Weiss; Allyson M. Pollock (Kerman University of Medical Sciences, 2016)
Background Good drug regulation requires an effective system for monitoring and inspection of manufacturing and sales units. In India, despite widespread agreement on this principle, ongoing shortages of drug inspectors have been identified by national committees since 1975. The growth of India's pharmaceutical industry and its large export market makes the problem more acute. Methods The focus of this study is a case study of Maharashtra, which has 29% of India's manufacturing units and 38% of its medicines exports. India's regulations were reviewed, comparing international, national and state inspection norms with the actual number of inspectors and inspections. Twenty-six key informant interviews were conducted to ascertain the causes of the shortfall. Results In 2009-2010, 55% of the sanctioned posts of drug inspectors in Maharashtra were vacant. This resulted in a shortfall of 83%, based on the Mashelkar Committee's recommendations. Less than a quarter of the required inspections of manufacturing and sales units were undertaken. The Indian Drugs and Cosmetics Act and its Rules and Regulations make no provisions for drug inspectors and workforce planning norms, despite the growth and increasing complexity of India's pharmaceutical industry. Conclusion The Maharashtra Food and Drug Administration (FDA) falls short of the Mashelkar Committee's recommended workforce planning norms. Legislation and political and operational support are required to produce needed changes.